Unveiling the Intellectual Structure of Investment Opportunity Set (IOS) Research: A Bibliometric Assessment of Corporate Finance Literature - Loso Judijanto (Eastasouth Institute, 2026)
This paper endeavors to shed light on the intellectual framework and trajectory of Investment Opportunity Set (IOS) studies in the literature of corporate finance using a bibliometric analysis. Through using publication statistics obtained from Scopus, a citation analysis, co-author analysis, and co-citation analysis, and analysis of co-occurrences of keywords have been performed. The results show that IOS studies have strong roots in mainstream corporate finance streams of profitability analysis, capital structure analysis, dividend policy analysis, and growth theory and have evolved into strategic management studies, sustainability, and technology support for decision-making, as well as policy-based investment analysis. Through interlinking loosely connected IOS literature into a unified intellectual framework and landscape, this paper can help in theory-building exercises and can be of great help to researchers aiming to position their forthcoming studies within a dynamic framework of corporate finance literature.